The cultural non-participant: critical logics and discursive subject identities. (7th May 2019) - Stevenson, David
Abstract : Purpose: The existence of so-called non-participants is a cultural policy problem in the UK and beyond. Yet, the very notion of a cultural non-participant seems nonsensical against the palpable evidence of lived experience. The purpose of this paper is to understand "who" a cultural non-participant is by first comprehending "what" the cultural non-participant is and why it exists. Design/methodology/approach: Drawing on primary data generated in the form of 40 in-depth qualitative interviews, this paper employs a discursive methodology to explore the critical logics (Howarth, 2010) that underlie the problem representation (Bacchi, 2009) of cultural non-participation and in particular the discursive subject identity of the cultural non-participant. Findings: Beginning with a discussion about how cultural non-participants are represented as socially deprived and hard to reach, the paper moves on to highlight how they are also presumed to lack knowledge and understanding about what they are rejecting. Their supposed flawed subjectivity is then contrasted with the desirable model of agency claimed by the cultural professionals who seek to change the cultural participation patterns of others. The paper concludes with a consideration of how the existence of the cultural non-participant subject identity limits the extent to which those labelled as such can meaningfully contribute to the field of cultural policy and obscures the extent to which such individuals are culturally disenfranchised. Research limitations/implications: Because of the chosen research approach and the geographical limitations to the data generation, the research makes no claim to generalisability. Therefore, researchers are encouraged to test the discursive logics identified at alternative discursive sites. Practical implications: This paper proposes a change in the language used by cultural professionals accompanied by changes in practice that abandoning the identity of the cultural non-participant would demand. Originality/value: This paper challenges a taken for granted assumption that cultural non-participants exist "in the real".